Transcriptional and neurotransmitter signatures of cerebral spontaneous neural activity in nurses with burnout - Song, Chun-Mei; Liu, Jian-Ping; Yang, Hu-Cheng; Li, Qing-He; Wang, Shu; Chen, Hai-Juan; Wang, Shu-Fang; Chen, Li; Gu, Si-Yu; Zhang, Feng; Pan, Ping-Lei (Frontiers in Public Health, 2025)
ObjectiveTo investigate the neural and molecular correlates of occupational burnout in nurses by integrating resting-state fMRI (rs-fMRI), clinical assessments, brain-wide gene expression, and neurotransmitter atlases.MethodsFifty-one female nurses meeting burnout criteria and 51 matched healthy controls underwent 3 T rs-fMRI. We analyzed fractional amplitude of low-frequency fluctuations (fALFF) and seed-based functional connectivity (FC), correlating findings with burnout (emotional exhaustion [EE], depersonalization [DP], and personal accomplishment [PA]). The fALFF t-map was spatially correlated with Allen Human Brain Atlas gene expression (followed by gene ontology enrichment) and neurotransmitter system maps.ResultsNurses with burnout exhibited significantly decreased precuneus fALFF and reduced precuneus-right dorsolateral prefrontal cortex (DLPFC) FC compared to controls. The fALFF in the precuneus negatively correlated with EE and DP, and positively correlated with PA, while reduced precuneus-DLPFC FC negatively correlated with EE. Genes spatially associated with fALFF alterations were enriched in pathways involving neuronal excitability, synaptic organization, stress response, and immune modulation. The fALFF alteration pattern also spatially correlated with serotonin, norepinephrine, γ-aminobutyric acid, glutamate, and endocannabinoid system distributions.ConclusionNurse burnout features precuneus hypoactivity and precuneus-DLPFC hypoconnectivity, linked to EE and DP severity. Associated molecular signatures implicate altered neuronal excitability, stress/immune pathways, and multiple neurotransmitter systems. The precuneus-DLPFC circuit and identified molecular pathways represent potential targets for interventions against burnout.